2022
DOI: 10.1007/s00468-022-02270-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and recommendations for management of trees and shrubs in green squares in Warsaw based on research on fungal diseases

Abstract: Key message Comprehensive management of urban greenery is a key approach to control fungal diseases of trees and shrubs to avoid the deterioration in their health status. Abstract Preliminary investigations on the health status related to fungal diseases of trees and shrubs growing in four green squares in Warsaw were conducted in 2017–2019. The examined plants were affected by diseases that are commonly identified in urban greenery, e.g., powdery mildew (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Protection of plants against the effects of diseases requires complex management. Guidelines should be based on good practices of plant monitoring and application of relevant recommendations for a comprehensive and sustainable strategy [ 36 ]. Effective management recommendations include regular monitoring, which facilitates rapid detection and identification of diseases, the use of innovative tools for mapping and creating digital databases of pathogens, systematic removal of fallen infected parts of plants, and burning removed parts of infected plants [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protection of plants against the effects of diseases requires complex management. Guidelines should be based on good practices of plant monitoring and application of relevant recommendations for a comprehensive and sustainable strategy [ 36 ]. Effective management recommendations include regular monitoring, which facilitates rapid detection and identification of diseases, the use of innovative tools for mapping and creating digital databases of pathogens, systematic removal of fallen infected parts of plants, and burning removed parts of infected plants [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many species are pathogens specialized to infect a variety of crops, orchards, ornamentals, or commercial plants (Ogórek et al, 2011). In Poland, the most common species is Alternaria alternata (Kimic et al, 2023). It is a polyphage that can be found on cereals and causes cereal black spot disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most literature deals with leaf disease development (Filipp et al, 2012; Fitzner & Fischer, 2005; Jones & Aldwinckle, 1997; Kalisz et al, 2015; Schildberger, 2011). A few sources mention infection on shoots (Cherniy, 2019; Hunt & O'Reilly, 1978; Kimic et al, 2022) and fruit (Mitrofanova, 1970), which is why pathogen development on shoots was studied. This is the first long‐term study of European juniper rust, carried out over 13 years under field conditions, against a background of natural infection, including leaf and shoot studies of pears.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all spores can infect pears, even a small amount of inoculum can cause a rust epidemic (Schildberger, 2011). The spores enter the host through the parenchyma, and the first symptoms of European pear rust appear after a specific time (Kimic et al, 2022). Throughout the study period, the first symptoms of European pear rust on pear leaves were observed at the end of May, whereas a massive onset of symptoms was observed in the first ten days of June.…”
Section: Discussionmentioning
confidence: 99%